The potential use of Indian rice flour or husk in fortification of pan bread: assessing bread’s quality using sensory, physicochemical, and chemometric methods - Elkatry, Haiam O.; El-Beltagi, Hossam S.; Ahmed, Abdelrahman R.; Mohamed, Heba I.; Al-Otaibi, Hala Hazam; Ramadan, Khaled M. A.; Mahmoud, Mohamed A. A. (Frontiers in Nutrition, 2023)
Hassawi rice is an Indica variety cultivated in Saudi Arabia with a higher nutritional value than the commercial Basmati rice varieties. The present study has investigated the feasibility of combining Hassawi rice flour (HRF) or husk (HRHF), an abundant byproduct, with wheat flour to produce nutritious economical pan bread. To achieve this aim, the physicochemical properties of HRF and HRHF were assessed using techniques such as UPLC-Tandem MS, ICP-OES, and colorimeter. The This is a provisional file, not the final typeset article proximate composition (moisture, crude fiber, and ash) and mineral contents of HRHF are significantly (p < 0.05) higher than HRF. On the other hand, the compounds p-coumaric acid, vanillic acid, γand δ-tocotrienols, and γ-oryzanol were unique to HRF. We further determined the changes in sensory, technological, and physicochemical properties of wheat flour bread substituted with 5, 10, and 15% of HRF or HRHF. The rheological tests showed that the addition of HRF and HRHF increased dough development and stability time. Further, substituting wheat flour for HRF and HRHF at levels higher than 10% affected sensory attributes, such as color, taste, odor, flavor, and appearance. These changes, however, were not always at a significant level. The causes of the differences in properties between control and fortified bread samples were investigated by chemometric methods. Samples of bread +HRF at 5 and 10% had comparable overall profiles to the control. On the other hand, bread +HRHF samples proved to retain higher concentrations of bioactive molecules compared to the control bread. Our findings shed light on the possible use of rice husk fibers in baking goods, notably pan bread. Furthermore, by integrating rice husk fibers into baked goods, we may boost their health benefits while also contributing to the long-term use of agricultural waste.